Contingency Linkages Between Strategy and General Manager Characteristics: A Conceptual Examination - Gupta, Anil K. (Academy of Management Review, 1984)
Prior research relating general manager characteristics to organizational strategy has (a) tended to operationalize these characteristics in vague and untestable terms; (b) focused almost solely on the implications of differences in business unit level strategic mission; and (c) rarely examined strategy-general manager linkages in the context of a key criterion variable, namely, effectiveness. This paper develops specific testable propositions that link six managerial characteristics to strategy and effectiveness at two hierarchical levels: corporate and strategic business unit.